Transporte de frangos: modificações do layout da carga como método de atenuação do estresse térmico - Pinheiro, Daniel Gurgel (2019)
Animal transportation is one of the most challenging topics in the area of animal ambience and well-being, which has, as the fundamental problem, the control of stressors in order to provide a comfortable environment for animals. The thermal stress caused by the combined action of temperature and relative humidity is the main responsible for losses during the transport of birds, causing losses to producers, as well. This is due to transportation issues, in its turn characterized by the confinement of birds in transport containers, which are arranged in the form of a compact prismatic load, along the body of a truck, making it difficult for wind to circulate inside. Therefore, regions of heat concentration usually take place. Thus, the purpose of this work was to analyse how changes in the load layout, with the use of devices to control the wind and devices to decompress the load (spacers) can contribute to minimize the effects of thermal stress. Computer-aided design and engineering tools were used, as well as fluid dynamics simulation tools; also, qualitative and quantitative tests in a wind tunnel with small scale models and statistically analysed methods. The information obtained was intriguing because it shows the complexity and the interaction of the variables involved in the transport operation, the unpacking and the new arrangement of the transport containers along the load. In general, the decompression of the load contributed to the increase of wind circulation throughout the load. The arrangement of the transport containers in the longitudinal position, the use of spacers and the greater distance between the rows of transport containers showed the best conditions for wind circulation throughout the load. However, it is clear that changing the layout does not guarantee that the wind will reach the birds, that is, it does not guarantee that the wind will circulate inside the transport containers so that the thermal exchange mechanisms can work efficiently. This result leads to the assumption that the design of the transport containers must be modified.